ANALISIS ALOKASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH RUMAH SAKIT UMUM DAERAH KABUPATEN NABIRE PROVINSI PAPUA, 2006-2011 - , Marthen George Erari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The study aimed to analyze the income and expenses budget allocation of the province hospital of Nabire District, Papua period 2006-2011 that was proposed and failed to be approved, which were proposed allocation, limit and considered as big realization, ratio of limit-proposed budget, ratio of realizationlimit budget, and ratio of realization-proposed budget. With the data of APBN during six years budget and numeric descriptive statistic analysis method, the results shown that the unapproved proposed budget was 46.95 billion rupiahs